Techno-economic analysis of the co-gasification of sewage sludge and petroleum coke - Adeyemi, Idowu; Khan, Haider; Ghenai, Chaouki; Janajreh, Isam (Frontiers in Sustainability, 2023)
In this study, the co-gasification of sewage sludge and petroleum coke is assessed with equilibrium and numerical modeling. The gasification process of these binary wastes provides a potential pathway for waste management and environmental sustainability. First, the thermodynamic equilibrium approach is used to calculate the maximum cold gasification efficiency (CGE) at different mixture ratios in an attempt to narrow down and focus on the appropriate composition of the two kinds of feedstock within the entrained flow gasifier. Furthermore, a parametric study is conducted to show the gasification metrics, i.e., CGE and feedstock conversion, and the syngas composition at different gasification conditions. The equilibrium model is based on eight unknowns in the gasification product, namely, H2, CO, CO2, H2O, CH4, O2, Csolid, and the temperature, under variable O2 and H2O molar ratios. Using three elemental mass balances, four equilibrium (Csolid) constant relations, and energy balance, the mathematical model is developed. The model incorporates the solid unburnt carbon in the product species. The temperature of gasification is determined through an iterative process. Using the result of the equilibrium model, a high-fidelity reactive flow model that accounts for the reactor geometry and the devolatilization kinetics is developed. This model accounts for an extended set of reactions covering the char combustion, water and gas shifts, Boudouard and devolatilization. Finally, economic analysis is carried out to assess the conditions when such a process can be deemed to be profitable. The result of the model shows that the maximum CGE is achieved when all the solid carbon is converted into carbon monoxide with nearly all hydrogen present in the feedstock converted into hydrogen gas. The maximum conversion was attained with sewage sludge and petroleum coke ratio of 1 at 1,200°C. The mole fraction of the syngas species obtained is XH2 = 0.4227 and XCO = 0.5774 and a small fraction of XCH4 = 0.0123. Moreover, the cold gasification efficiency (CGE) measures 87.02% for the H2 and CO syngas species and reached 91.11% for the three species, including CH4. The gasification of the sewage sludge and petroleum coke at 50:50 is economically viable at temperatures higher than 950°C. A peak net gain of 0.16 /kg of fuel blend was achieved at 1,250°C. At temperatures lower than 950°C, net losses were realized. This could be associated with less product gas yield, which is not significant enough to counteract the input costs. For instance, the net losses were −0.03 and −0.17 /kg of feedstock at 950 and 800°C, respectively.